Two new species of the spider genus Poeciloneta Kulczyn’ski, 1894 (Araneae: Linyphiidae) from China - Zhai, Hui; Zhu, Ming-Sheng (Zootaxa, 2008)
The genus Poeciloneta was erected by Kulczyn’ski (Chyzer & Kulczyn’ski, 1894) with Neriene variegata Blackwall, 1841 as the type species. Poeciloneta includes 15 species and two of them occur in China: P. variegata (Blackwall, 1841) and P. hengshanensis (Chen & Yin, 2000), which distribution in Xizang, Xinjiang and Hunan province. Whereas,there is no modern revision of the genus recently.